2016
DOI: 10.1007/s10029-016-1492-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of transforming growth factor beta 1 in communicating and non-communicating hydrocele

Abstract: The amount of TGF-β1 was higher in HC fluid than in non-communicating. To investigate the role of cytokine in the closure of PV, further studies will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This theory has been tested on hernia sacs, but the peptide only increased the level of the growth factor in some samples ( 32 ). It is still unclear if deficient endogenous calcitonin gene-related peptide disrupts obliteration of processus vaginalis ( 32 ) or if obliteration is regulated through other mechanisms such as transforming growth factor β-1, which stimulates fibrosis ( 48 ). Detailed investigations in humans have been hindered due to issues with finding proper animal models with patent processus vaginalis ( 49 ).…”
Section: Processus Vaginalismentioning
confidence: 99%
“…This theory has been tested on hernia sacs, but the peptide only increased the level of the growth factor in some samples ( 32 ). It is still unclear if deficient endogenous calcitonin gene-related peptide disrupts obliteration of processus vaginalis ( 32 ) or if obliteration is regulated through other mechanisms such as transforming growth factor β-1, which stimulates fibrosis ( 48 ). Detailed investigations in humans have been hindered due to issues with finding proper animal models with patent processus vaginalis ( 49 ).…”
Section: Processus Vaginalismentioning
confidence: 99%
“…TGF-b1 is a potent fibrogenic agent and stimulates fibrosis of processus vaginalis. Mosavi, et al have observed that the amount of TGF-b1 was higher in communicating hydrocele fluid than in non-communicating hydrocele [ 15 ]. Further studies on the role of cytokines may provide insight into the exact mechanism of obliteration of processus vaginalis.…”
Section: Discussionmentioning
confidence: 99%